2015
DOI: 10.3928/1081597x-20150319-03
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Lens Power Selection and Positioning With and Without Intraoperative Aberrometry

Abstract: Patients undergoing cataract extraction with toric IOL placement aided by intraoperative aberrometry were 2.4 times more likely to have less than 0.50 D of RRA compared to standard methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 13 publications
1
40
0
6
Order By: Relevance
“…We also did not use intraoperative aberrometry 19 or a ray-tracing method, such as the one suggested by Hoffmann et al 14 Additional studies comparing the Abulafia-Koch formula adjustments and the Barrett IOL calculator to intraoperative aberrometry and to devices that directly measure the net corneal astigmatism by a ray-tracing approach are warranted. An additional limitation of our study is that we validated the Abulafia-Koch formula using IOLMaster measurements.…”
Section: Methods Of Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…We also did not use intraoperative aberrometry 19 or a ray-tracing method, such as the one suggested by Hoffmann et al 14 Additional studies comparing the Abulafia-Koch formula adjustments and the Barrett IOL calculator to intraoperative aberrometry and to devices that directly measure the net corneal astigmatism by a ray-tracing approach are warranted. An additional limitation of our study is that we validated the Abulafia-Koch formula using IOLMaster measurements.…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…However, several studies recently reported that methods of calculation that account for posterior corneal astigmatism might be more appropriate for toric IOL calculations. Those methods apply nomograms, 13 coefficients of adjustment, 6 direct measurements of the posterior cornea, 10,18 a ray-tracing approach using combined keratometry and tomography data, 14 intraoperative aberrometry, 19 and mathematic models. 12 The purpose of this study was to describe a new regression formula that can calculate the estimated total corneal astigmatism using standard keratometry (K) measurements and to compare the error in the predicted residual astigmatism of 2 representative toric IOL calculators with and without the use of the new formula.…”
mentioning
confidence: 99%
“…Potential causes of this include patient factors (such as eyelid squeezing, eye motion, healing), surgical equipment or devices (such as the eyelid speculum or use of certain ophthalmic viscosurgical devices) and/or intraoperative manipulation (such as stromal hydration); these factors can change intraocular pressure and axial length, corneal thickness and the refractive index of the anterior chamber 911. Studies suggest that these operative variables may be adequately controlled, especially with increased surgeon experience using IA 3,4. A more fundamental concern is the lack of measurement of the expected lens position (ELP), which is a significant factor affecting the power of an IOL.…”
Section: Introductionmentioning
confidence: 99%
“…The method of determining the steep axis at the time of IOL implantation is the key to successful implantation of a toric IOL. The recently developed image guided system to overlay the steep axis under the microscope and intraoperative aberrometry are expected to improve the accuracy of IOL alignment [20].…”
Section: Discussionmentioning
confidence: 99%